Highly dispersed NiCu nanoparticles on SBA-15 for selective hydrogenation of methyl levulinate to γ-valerolactone. (14th September 2020) - Fang, Cheng; Kuboon, Sanchai; Khemthong, Pongtanawat; Butburee, Teera; Chakthranont, Pongkarn; Itthibenchapong, Vorranutch; Kasamechonchung, Panita; Witoon, Thongthai; Faungnawakij, Kajornsak
Abstract: Copper and nickel nanoparticles highly dispersed on an ordered mesoporous silica support (SBA-15) were prepared by a glycol-assisted impregnation method and tested for the catalytic transfer hydrogenation reaction of methyl levulinate to γ-valerolactone (GVL). Characterizations by high resolution transmission electron microscopy, X-ray diffraction, N2 sorption, H2 temperature-programmed reduction and X-ray absorption spectroscopy confirm that the highly dispersed nanoparticles were well-anchored to the mesopores of SBA-15 with the strong interaction. Comparing to a catalyst synthesized by a conventional aqueous impregnation method, our catalyst shows a higher conversion and greater selectivity towards GVL of reaction at 140–170 °C using 2-propanol as a solvent and a hydrogen donor. Results showed that NiCu/SBA-15 (EG) had much better activity, providing 91.3% conversion of ML with 89.7% selectivity towards GVL in 3 h at 140 °C. The high compositional homogeneity, uniform distribution of the nanoparticles in the mesoporous channels and the strong interaction between the metal nanoparticles and SBA-15 contribute to the superior catalytic performance. This catalyst also demonstrates superb stability over the course of 5 reaction cycles without significant loss in catalytic activity and selectivity towards GVL formation. Graphical abstract: Image 1 Highlights: Glycol-assisted method impregnates well-dispersed Ni & Cu nanoparticles on support. Unlike water, glycol generates smaller, well-anchored, & homogenous nanoparticles. Ni & Cu nanoparticles on support is active and stable catalysts for γ-valerolactone production.